The interplay between dysregulated metabolites and signaling pathway alterations involved in osteoarthritis: a systematic review - Atiqah Aziz; Kavitha Ganesan Nathan; Tunku Kamarul; Ali Mobasheri; Alimohammad Sharifi (Therapeutic Advances in Musculoskeletal Disease)
Background: Osteoarthritis (OA) is a common degenerative joint disease that poses a significant global healthcare challenge due to its complexity and limited treatment options. Advances in metabolomics have provided insights into OA by identifying dysregulated metabolites and their connection to altered signaling pathways. However, a comprehensive understanding of these biomarkers in OA is still required. Objectives: This systematic review aims to identify metabolomics biomarkers associated with dysregulated signaling pathways in OA, using data from various biological samples, including in vitro models, animal studies, and human research. Design: A systematic review was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data sources and methods: Data were gathered from literature published between August 2017 and May 2024, using databases such as “PubMed,” “Scopus,” “Web of Science,” and “Google Scholar.” Studies were selected based on keywords like “metabolomics,” “osteoarthritis,” “amino acids,” “molecular markers,” “biomarkers,” “diagnostic markers,” “inflammatory cytokines,” “molecular signaling,” and “signal transduction.” The review focused on identifying key metabolites and their roles in OA-related pathways. Limitations include the potential exclusion of studies due to keyword selection and strict inclusion criteria. Results: The meta-analysis identified dysregulated metabolites and associated pathways, highlighting a distinct set of related metabolites consistently altered across the studies analyzed. The dysregulated metabolites, including amino acids, lipids, and carbohydrates, were found to play critical roles in inflammation, oxidative stress, and energy metabolism in OA. Metabolites such as alanine, lysine, and proline were frequently linked to pathways involved in inflammation, cartilage degradation, and apoptosis. Key pathways, including nuclear factor kappa B, mitogen-activated protein kinase, Wnt/β-catenin, and mammalian target of rapamycin, were associated with changes in metabolite levels, particularly in proinflammatory lipids and energy-related compounds. Conclusion: This review reveals a complex interplay between dysregulated metabolites and signaling pathways in OA, offering potential biomarkers and therapeutic targets. Further research is needed to explore the molecular mechanisms driving these changes and their implications for OA treatment.